###
Algebra Change of Subject 2(review)

y=x-(2x-1)(1/T) 1

y=[x(T-2)+1]/T 1

y=T+3x-1 1

y=T(2x-1)-x 1

y=1+T-x 1

y=-[T(2x-1)/x] 1

y=(Tx+1-2x)/T 1

y=(-2x+1/T)+x 1

y=(-2x+1+Tx)/T 1

y = (2x=1)*(x-T) 1

Tx/x=1/(-y)

-Tx/x=y

y=-Tx/x 1

Tx-Ty=2x-1

-Ty=2x-1-Tx

Ty=Tx+1-2x

y=(Tx+1-2x)/T 1

T=(((2x-1))/((x-y)))

(x-y)(T)=(2x-1)

xT-yT=2x-1

x-y=((2x-1)/(T))

y=-(x((2x-1)/(T))) 1

T=(2x-1)/(x-y)

T(2x-1)=x-y

2xT-T =x-y

2xT-T-x=-y

-x=y 1

T(x-y)=2x-1 1

(x-y)T=(2x-1)

(x-y)=(2x-1)/T

-y=[(2x-1)/T]-x

y=[(1+2x)/-T]+x 1

(2x-1)/T - x = y 1

Error: Tx-Ty=2x-1

ReplyDeleteExplain: Does not understand the change of subject clearly. y is not the subject in this equation.

Correct answer: y=(-2x+1+Tx)/T

This comment has been removed by the author.

ReplyDeleteError: -Tx/x=y

ReplyDeleteExplanation: Did not simplify 'x' properly. 'x' should have been implied further. Also, the negative should be passed to the 'y' instead of the subject, 'T'

Correct Answer: T = -y

Error 1

ReplyDeleteTx/x=1/(-y)

Explanation: 'y' is not the subject in the formula. Does not know how to change the subject of the question correctly. The formula is not complete yet

error: (x-y)=(2x-1)/T

ReplyDeleteExplanation: Does not understand the change of subject, y should have been the subject and not (x-y)=(2x-1)/T.

Correct answer: y=(-2+1+Tx)/T

Error: Tx-Ty=2x-1

ReplyDeleteExplanation: y is not the subject of this equation, thus it is not simplified to the simplest.

Correct answer: y=(-2+1+Tx)/T.

Error 1

ReplyDelete-Tx/x=y

explain: conceptual error, misunderstanding of question, the numbers were not considered

correct answer y = (-2x+1+Tx)/T

y = (2x=1)*(x-T) 1

ReplyDeletey=(2x=1) <---- that just doesn't make senses, i think the student pressed the wrong key and did not double check his/her answer

correct answer is y=(-2x+1+tx)/t

Error:-y=[(2x-1)/T]-x

ReplyDeleteExplanation:The student forget to change the negative 'y' into positive 'y' .

Correct answer: y=(Tx+1-2x)/t)

error:-y=[(2x-1)/T]-x

ReplyDeleteExplanation: This student changed the subject from y to -y which is wrong. He or she might have made a mistake when doing the sum and therefore get the wrong equation or might have seen the subject wrongly

Error:

ReplyDeleteTx-Ty=2x-1

Explain: Should continue to factorize further.

Correct answer: y=(-2+1+Tx)/T

ReplyDelete

Error: [ Tx-Ty=2x-1 ]

ReplyDeleteExplanation: Has not understood the change of subject clearly. y is not portrayed as the subject of this equation.

Correct answer: [ y = (-2x+1+Tx)/T ]

Error:-Ty=2x-1-Tx

ReplyDeleteExplain:-ty should not be the subject of the formula, but y instead.Some steps have been missed out.

Correct answer:y=(-2x+1+tx)/t

xT-yT=2x-1

ReplyDeleteExplanation: Y isn't the subject of this equation.

Ans: y = (-2x+1+Tx)/T

Error 1:

ReplyDeletey=(-2x+1+Tx)/T 1

y = (2x=1)*(x-T) 1

More steps than needed, cannot be factorised this way.

Error 2:

-Ty=2x-1-Tx

Ty=Tx+1-2x

Minus sign(-) cannot be only applied to one number, but to the whole side of the equation.

error:-y=[(2x-1)/T]-x

ReplyDeleteExplanation: This student changed the subject from y to -y which is wrong. He or she might have made a mistake when doing the sum and therefore get the wrong equation or might have seen the subject wrongly

Error:Tx-Ty=2x-1

ReplyDeleteexplanation: Y is supposed to be the subject hence it should be y= -(2x+1-Tx)/T

Error: Tx-Ty=2x-1

ReplyDeleteExplanation: y is supposed to be the subject, not -y, the student still has to multiply both sides of the equation to get y=1+Tx-2x